Tetraazamacrocyclic Schiff Base Co(II) and Ni(II) Complexes as Catalysts for Hydroxylation of Phenol - Bi, Jian-Hong (Asian Journal of Chemistry, 2011)
The catalytic activity of two tetraazamacrocyclic Schiff base complexes of Co(II) and Ni(II) with the composition CoL and NiL, respectively were studied by the liquid phase catalytic hydroxylation of phenol to catechol and hydroquinone using H2O2 as oxidant. In the presence of the catalysts, CoL and NiL, the 31.3 % phenol conversion was obtained with 52.6 % selectivity to benzenediol and the 33.6 % phenol conversion was obtained with 53.8 % selectivity to benzenediol under the optimum reaction conditions.